5C Credit Analysis, SLIK Utilization, and ICS Readiness Determine MSME Financing Access through Credit Decision - Eva Septriani Sianipar; Mokhamad Anwar; Asep Mulyana (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are key drivers of economic development but often face financing constraints due to limited collateral, weak credit histories, and information asymmetry. This study examines how 5C credit analysis, Financial Information Service System (SLIK) utilization, and Innovative Credit Scoring (ICS) readiness influence MSME credit decision-making and financing access in Rural Banks in North Sumatra, Indonesia. The study further investigates whether credit decision-making mediates the relationship between these assessment mechanisms and financing access. A quantitative survey was conducted with 290 credit decision-makers, including directors, branch managers, and credit officers. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate direct, indirect, and total effects among the constructs. The findings indicate that 5C credit analysis significantly influences credit decision-making but does not directly impact MSME financing access, with its effect fully mediated through credit decisions. In contrast, SLIK utilization and ICS readiness significantly affect both credit decision-making and financing access, with credit decisions partially mediating these relationships. Credit decision-making serves as the primary mechanism translating institutional assessment into actual financing, highlighting the importance of integrating traditional and digital credit assessment tools to support prudent and inclusive MSME financing in rural banks.